Pemikiran Ahmad Syafii Maarif tentang Negara dan Syariat Islam di Indonesia - Ahmad Asroni (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
The discourse of Islamic state and the implementation of the sharia (Islamic law) has been an endless issue to be discussed. This issue is still debatable for various parties. In one sense, it is accepted and even supported. In other sense, it is blasphemed and criticized. In the reality of global politics, the efforts to establish Islamic state and the implementation of the sharia has been practiced by many Islamic countries including Indonesia. This paper tries to explore Ahmad Syafii Maarif ’s thought concerning the discourse of Islamic state and the implementation of the sharia. Ahmad Syafii Maarif refuses the efforts to establish Islamic state and the implementation of the sharia by unconstitutional and undemocratic ways. He criticizes people promoting the discourse. Besides theological and historical reasons, he argues that the discourse will have no benefit. In his perspective, Islam is adequately positioned as an ethical foundation of nation.